THE ROLE OF BOOKS BY PRESIDENTS IN CREATING NEW SOCIETY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Books authored by presidents play a significant role in shaping societal values, policies, and discourse. This abstract explores the multifaceted impact of presidential writings on the creation of a new societal ethos. Through promoting ideals, setting policy agendas, educating citizens, and influencing national discourse, presidential books serve as pivotal tools for inspiring change and fostering civic engagement. They catalyze social change, strengthen diplomatic relations, and reflect evolving societal values. By leveraging the power of storytelling and personal narratives, presidents' literary contributions leave enduring imprints on the collective consciousness, guiding societies towards progress, unity, and shared prosperity. This abstract underscores the transformative influence of presidential books in shaping the fabric of modern societies.